Analysis of Anti-Tuberculosis Medication Adherence Among TB Patients in Private Medical Practices in Cirebon City - Hidayati, Nur Rahmi; Rinto Susilo; Setyaningsih, Indah (Universitas Muhammadiyah Surakarta, 2025)
Tuberculosis (TB) is a disease caused by infection with the bacterium Mycobacterium tuberculosis. This disease is highly contagious, so adherence to anti-TB treatment is very important. The aim of this study is to determine patient characteristics (gender, age, educational level, occupation, and duration of tuberculosis treatment), assess patient adherence to tuberculosis treatment, and examine the relationship between patient characteristics and medication adherence in private practice settings in the city of Cirebon. This type of research is non-experimental. Data collection was conducted prospectively using a tuberculosis patient characteristic questionnaire and MARS-5 questionnaire (Medication Adherence Report Scale-5). The sample consisted of all tuberculosis patients undergoing treatment at private medical practices in Cirebon City who met the inclusion criteria, totaling 108 respondents. The characteristics of tuberculosis patients at private medical practices in Cirebon City were predominantly male (58.3%), aged 45–59 years (33.3%), with a high school education level (47.2%), self-employed occupation (37,0%), and treatment duration < 1 year (71.3%). The rate of high treatment adherence was 67.6%. Based on the results of the Multivariate Logistic Regression statistical test, there was no significant relationship between gender (p=0.751), age (p=0.870), education level (p=0.364), occupation (p=0.779), and duration of treatment (p=0.897) with adherence to tuberculosis medication.